2008
DOI: 10.1016/j.jvs.2008.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance angiography of collateral blood supply to spinal cord in thoracic and thoracoabdominal aortic aneurysm patients

Abstract: Collateral arteries supplying the spinal cord can be systematically visualized using MRA. Spinal cord blood supply during open aortic surgery may crucially depend on collateral arteries. Preoperatively identified collateral supply was 97% predictive for stable intraoperative spinal cord function. Patients in whom no collaterals can be depicted preoperatively are at increased risk for spinal cord dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 20 publications
0
43
1
Order By: Relevance
“…On the other hand, MRA may overestimate stenosis, and stenosis of the segmental arteries at the orifice may be misunderstood as an occlusion. In reviewing our CTA data, we found that only 1 of 25 cases had occlusion of the segmental artery directly connecting to the AKA, the rate (1/25) was much lower than the result by Backes et al, 1 and 4 had significant stenosis that might have appeared to be occluded on MRA. The scanning field of MRA is limited to 5 to 6 cm in the left-to-right orientation, and MRA can miss collaterals (eg, through the intercostal artery 3 or the internal thoracic artery 4 ).…”
contrasting
confidence: 60%
“…On the other hand, MRA may overestimate stenosis, and stenosis of the segmental arteries at the orifice may be misunderstood as an occlusion. In reviewing our CTA data, we found that only 1 of 25 cases had occlusion of the segmental artery directly connecting to the AKA, the rate (1/25) was much lower than the result by Backes et al, 1 and 4 had significant stenosis that might have appeared to be occluded on MRA. The scanning field of MRA is limited to 5 to 6 cm in the left-to-right orientation, and MRA can miss collaterals (eg, through the intercostal artery 3 or the internal thoracic artery 4 ).…”
contrasting
confidence: 60%
“…Pre-operative planning should include a CTA or MRA evaluation of the spinal cord circulation including lower lumbar and pelvic arteries, which play a major role in spinal cord blood supply in 16% and 8% of cases, respectively. 198,199 The pre-operative assessments of cardiac, pulmonary, and renal function, as well as carotid and peripheral arterial occlusive disease are essential to minimize the risks of mortality and morbidity associated with DTAA repair. Additional studies such as echocardiography, cardiac catheterisation, and, in selected cases, Holter 24-hour electrocardiography monitoring, are usually requested for patients with a history of coronary or valvular heart disease.…”
Section: Recommenda On 39mentioning
confidence: 99%
“…4,5,[10][11][12][13] The use of these imaging techniques for preoperative analysis and surgical planning enables selective reconstruction of the feeding radiculomedullary artery. 4,5,14 However, it is di‹cult to reconstruct the artery of Adamkiewicz itself because of its small size (about 0.5 mm in diameter) and its branching from the intercostal/lumbar artery at the intervertebral foramen.…”
Section: Discussionmentioning
confidence: 99%
“…Collateral arteries feeding into the artery of Adamkiewicz may enhance the detection of the arterial vasculature branching from the aorta. It is still controversial that the collateral vessels can feed blood into the spinal cord, 13,15 and occlusion of the artery of Adamkiewicz may not be the only causative factor aŠecting spinal ischemia. 16 However, actual cases of spinal cord ischemia after endovascular repair of the aorta continue to be reported, 17 and increase in biochemical markers of ischemic spinal cord injury was documented in an experimental canine study of stent-graft implantation at a critical aortic segment.…”
Section: Discussionmentioning
confidence: 99%